THE ADAPTIVE METHOD OF PROBABILISTIC-ALGEBRAIC SIMULATION CONTROLLED PROCESSES WITH POTENTIAL HAZARDS ELEMENTS - V. S. Smorodin; E. I. Sukach; Y. V. Zherdetsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The method of probabilistic-algebraic simulation driven technological production processes with the potential danger elements, based on the conduct of proactive modeling using parameterized probabilistic-algebraic models is described, which is used for assessing the behavior of the object in the dynamics and thus improving the description adequacy of real processes of potential danger elements interaction during realization of the production cycle.